2012
DOI: 10.1097/cji.0b013e3182661afa
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Macrophage Differentiation and Polarization of Tumor-associated Macrophages Towards M1 Subtype in Listeria-administered Tumor-bearing Host

Abstract: This study investigates the effect of Listeria administration on differentiation of macrophages from precursor bone marrow cells and functional status of tumor-associated macrophages (TAM). Listeria administration not only resulted in an augmented infiltration of tumor by F4/80 macrophages but also repolarized the functional status of TAM displaying features of some M1 macrophage subtype with upregulated phagocytosis and tumoricidal activity accompanied by altered expression of monocarboxylate transporter-1, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Typically, tumor-associated macrophages are polarized towards an M2-like state and provide support for tumor growth and progression (27,39). Consistent with the decrease in TGFβ, we discovered that DX-2400 induced M1-like macrophages that could contribute to primary tumor growth delay.…”
Section: Discussionsupporting
confidence: 73%
“…Typically, tumor-associated macrophages are polarized towards an M2-like state and provide support for tumor growth and progression (27,39). Consistent with the decrease in TGFβ, we discovered that DX-2400 induced M1-like macrophages that could contribute to primary tumor growth delay.…”
Section: Discussionsupporting
confidence: 73%
“…In addition, subcutaneous xenograft nude mouse models confirmed that the growth of tumours was weakened by knock‐down MMP14 and INHBA. Therefore, macrophage M2 cells may support cancer progression and tumour growth 24,25 …”
Section: Discussionmentioning
confidence: 99%
“…GM1 ganglioside, an a-series ganglioside containing a single sialic acid residue, is the most widely used marker for lipid rafts in the plasma membrane [36]. Like other glycoconjugates, GM1 shed from cells mediates its biological function via interaction with soluble or membrane-bound molecules outside the cell ( trans -interaction), or via influence on the proteins within the same membrane ( cis -interaction) [25, 37] after incorporation into the lipid bilayer of the plasma membrane [38].…”
Section: Discussionmentioning
confidence: 99%